Cleavage of cruciform DNA structures by an activity from Saccharomyces cerevisiae. - West, S C (1985)
Protein extracts from Saccharomyces cerevisiae have been fractionated to reveal a nuclease activity that cleaves cruciform structures in DNA. Negatively supercoiled plasmids that contain inverted repeats that are extruded into cruciform structures have been used as DNA substrates. The sites of cleavage of pColIR215 DNA are located within the extruded cruciform stems and are symmetrically opposed to each other across the cruciform junction. Neither relaxed duplex DNA nor single-stranded DNA serve as substrates. The native molecular weight of the activity was estimated to be approximately equal to 200,000 by gel filtration.